Design of a Metallacycle‐Based Supramolecular Photosensitizer for In Vivo Image‐Guided Photodynamic Inactivation of Bacteria. Issue 5 (17th December 2021) - Xu, Yuling; Tuo, Wei; Yang, Liang; Sun, Yan; Li, Chonglu; Chen, Xiaoqiang; Yang, Wenchao; Yang, Guangfu; Stang, Peter J.; Sun, Yao
Abstract: Bacterial infection is one of the greatest threats to public health. In vivo real‐time monitoring and effective treatment of infected sites through non‐invasive techniques, remain a challenge. Herein, we designed a Pt II metallacycle‐based supramolecular photosensitizer through the host‐guest interaction between a pillar[5]arene‐modified metallacycle and 1‐butyl‐4‐[4‐(diphenylamino)styryl]pyridinium. Leveraging the aggregation‐induced emission supramolecular photosensitizer, we improved fluorescence performance and antimicrobial photodynamic inactivation. In vivo studies revealed that it displayed precise fluorescence tracking of S. aureus ‐infected sites, and in situ performed image‐guided efficient PDI of S. aureus without noticeable side effects. These results demonstrated that metallacycle combined with host‐guest chemistry could provide a paradigm for the development of powerful photosensitizers for biomedicine. Abstract : A metallacycle‐based supramolecular photosensitizer (1⊃2 ) for in vivo image‐guided photodynamic inactivation of bacteria is reported. Through host‐guest interaction, the assembly 1⊃2, with improved fluorescence signals and ROS production capabilities, is employed for in vivo fluorescence tracking as well as accurate image‐guided treatment of S. aureus infection without noticeable side effects.